Evaluation of smartphone addiction and related factors among university students - Akbulut Zencirci, Sevil; Aygar, Hatice; Göktaş, Saniye; Önsüz, Muhammed Fatih; Alaiye, Melike; Metintaş, Selma (International Journal of Research in Medical Sciences, 2018)
Background: The purpose of this study is to investigate the level of smartphone addiction of university students and determine the related factors. Methods: This cross-sectional study was conducted among first and third-class students of the 2016 fall semester in Eskişehir Osmangazi University with 1492 students. In this study, risk of smartphone addiction was evaluated by using Short Version of Smartphone Addiction Scale (SAS-SV). In data analysis, Mann Whitney U, Kruskal Wallis and hierarchical multi linear regression analysis were executed. Results: 772 (51.7 %) of 1492 students in the study group was female. SAS-SV median score of the students was 26. In this study; gender, socio-economic level, perceived health status and mostly used smartphone function were specified as factors influencing smartphone addiction. While, using smartphone for functions such as social media, gaming, online messaging and video watching was assigned to be positively related with smartphone addiction; using smartphone for telephone calls, e-mail and news reading was assigned to be negatively related. 71.2% of students (n:1063) declared to have health problems related with using smartphones. Insomnia was revealed as the most common (23.6 %) health complaint related to smartphone use. Conclusions: Social contact and applications with entertaining contents in smartphone enhance addiction. There is need for more studies and researches for exerting smartphone addiction, related factors and applying necessary protective and therapeutic interventions.